Biomarker potential of ST6GALNAC3 and ZNF660 promoter hypermethylation in prostate cancer tissue and liquid biopsies. Issue 4 (13th March 2018) - Haldrup, Christa; Pedersen, Anne L.; Øgaard, Nadia; Strand, Siri H.; Høyer, Søren; Borre, Michael; Ørntoft, Torben F.; Sørensen, Karina D.
Abstract : Current diagnostic and prognostic tools for prostate cancer (PC) are suboptimal, leading to overdiagnosis and overtreatment. Aberrant promoter hypermethylation of specific genes has been suggested as novel candidate biomarkers for PC that may improve diagnosis and prognosis. We here analyzed ST6GALNAC3 and ZNF660 promoter methylation in prostate tissues, and ST6GALNAC3, ZNF660, CCDC181, and HAPLN3 promoter methylation in liquid biopsies. First, using four independent patient sample sets, including a total of 110 nonmalignant (NM) and 705 PC tissue samples, analyzed by methylation‐specific qPCR or methylation array, we found that hypermethylation of ST6GALNAC3 and ZNF660 was highly cancer‐specific with areas under the curve (AUC) of receiver operating characteristic (ROC) curve analysis of 0.917–0.995 and 0.846–0.903, respectively. Furthermore, ZNF660 hypermethylation was significantly associated with biochemical recurrence in two radical prostatectomy (RP) cohorts of 158 and 392 patients and remained significant also in the subsets of patients with Gleason score ≤7 (univariate Cox regression and log‐rank tests, P < 0.05), suggesting that ZNF660 methylation analysis can potentially help to stratify low‐/intermediate‐grade PCs into indolent vs. more aggressive subtypes. Notably, ZNF660 hypermethylation was also significantly associated with poor overall and PC‐specific survival in the RP cohort ( n = 158) with long clinical follow‐up available. Moreover, as proof of principle, we successfully detected highly PC‐specific hypermethylated circulating tumor DNA (ctDNA) for ST6GALNAC3, ZNF660, HAPLN3, and CCDC181 in liquid biopsies (serum) from 27 patients with PC vs. 10 patients with BPH, using droplet digital methylation‐specific PCR analysis. Finally, we generated a three‐gene ( ST6GALNAC3 / CCDC181 / HAPLN3 ) ctDNA hypermethylation model, which detected PC with 100% specificity and 67% sensitivity. In conclusion, we here for the first time demonstrate diagnostic biomarker potential of ST6GALNAC3 and ZNF660 methylation, as well as prognostic biomarker potential of ZNF660 . Furthermore, we show that hypermethylation of four genes can be detected in ctDNA in liquid biopsies (serum) from patients with PC. Abstract : In this large‐scale study, we identified ST6GALNAC3 and ZNF660 promoter methylation as potential diagnostic biomarkers for prostate cancer (PC) by molecular analyses of malignant and benign prostate tissue samples from more than 800 patients. Furthermore, we identify ZNF660 hypermethylation as associated with increased risk of biochemical recurrence, as well as with reduced overall survival and reduced PC‐specific survival, thus showing promising prognostic potential. In addition, as proof of principle, we demonstrate hypermethylation of ST6GALNAC3, ZNF660, CCDC181, and HAPLN3 in liquid biopsies from patients with PC and identify a three‐gene panel with 100% specificity and 67% sensitivity for PC, suggesting a high potential as novel minimally invasive ctDNA methylation markers for PC.